(untitled) (MASKAY, 2012)
The analysis, modeling, and design of a control loop for photovoltaic (PV) systems connected to the electrical network is described. The modeling of a photovoltaic panel is approached; the design of a boost converter (Boost) and its control loop using a proportional-integral PI current controller and a slider mode controller; and finally, the design of a single-phase DC-AC inverter. A description of the Boost converter dynamics and the equations for the sliding mode control for a single-phase inverter is presented. The proposed system has been simulated using the Matlab/Simulink SimPowerSystems library tools.